Effect of Light on Seed Germination of Some Tropical and Temperate Species of Nepal - Kafle, Rashika; Thapa Magar, Madhu Shudan; Lamichhane, Dipak; Chaudhary, Tulasa; Parmar, Gaurav (Nepal Journal of Botany, 2025)
Seed germination is a fundamental process in plant development, influenced by both intrinsic and extrinsic factors. Light and dark have quite diverse effects on seed germination in different plant species under different environmental conditions. This study aimed to determine the lag period and germination speed (t50) of seeds of 37 plant species under light and dark conditions with a standard temperature of 25°C in light/alternating dark at 15°C with a 12-hour alternating photoperiod and 75% relative humidity in a plant growth chamber. The statistical analysis did not reveal any significant impact of light treatment on seed germination percentage across different plant life forms. However, a higher percentage of species (52%) exhibited the germination class >75% in light, compared to 43% in dark. The lag period of 38% of species was very short (<8 days), and 30% of the species had very fast (<8 days) germination speed (t50). In addition, the lag period and germination speed (t50) values were found to be comparable. This study may contribute to unveiling the viability and regeneration potential of seeds, which is a prerequisite for storage in the seed bank.